Lupus - Peeters, Frederik (Top Shelf, 2019)
"Award-winning Swiss graphic novelist Frederik Peeters soars to new heights with an existential interplanetary epic that never strays far from the human heart. Lupus Lablennorre is a man on the run. Like a cosmic Odysseus, he wanders from planet to planet, haunted by his past and orbiting around a woman. It starts as a fishing trip with his old pal, Tony. Their friendship has started to feel different lately, and not just because of the drugs. Picking up Sanaa, a beautiful runaway, only complicates the situation. When tragedy strikes, they're forced to flee to new worlds, each offering many ways to disappear. But Lupus will find that the tendrils of friendship, love, and family are not so easily severed. Armed with astonishingly expressive brushwork and a dreamy, intimate narrative, Frederik Peeters drifts on the solar winds to a new understanding of memory, guilt, isolation, and connection."--Publisher's website.